Bauchi State Agricultural Development Programme (B.S.A.D.P.): breifing notes - Bauchi State Agricultural Development Programme (Bauchi: Bauchi State Agricultural Development Programme (B.S.A.D.P.), 1979)
This is a brief summary of the agricultural development potentials of Bauchi state of Nigeria
osc 21/05/2019
Arch
Keywords: Agricultural Economics; Agricultural production; Bauchi, Nigeria